Penerapan Model Pembelajaran Mastery Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas V SD Negeri 40 Seluma, Bengkulu - Hendri Kelana; Sismidarti; Asiyah (Edification Journal : Pendidikan Agama Islam, 2026)
This study aims to improve students’ learning outcomes in Islamic Religious Education (PAI), particularly on the topic of the procedures of Tarawih prayer, through the implementation of the Mastery Learning model in Grade V of SD Negeri 40 Seluma, Bengkulu. The research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection. The participants were 18 fifth-grade students, including 8 male and 10 female students. Data were collected through observation, interviews, practical tests, and documentation. The analysis used descriptive quantitative techniques with percentage calculations to measure students’ learning achievement and learning activity. The findings showed a significant improvement in students’ learning outcomes after the implementation of the Mastery Learning model. Classical learning mastery increased from 38.89% in the pre-cycle to 55.56% in Cycle I, and further to 83.33% in Cycle II. The proportion of students who had not yet achieved mastery decreased from 61.11% in the pre-cycle to 44.44% in Cycle I and 16.67% in Cycle II, indicating that the implementation of Mastery Learning effectively improved students’ learning outcomes and participation in Islamic Religious Education. These results indicate that the Mastery Learning model effectively enhances students’ learning outcomes and engagement in Islamic Religious Education.